Association between Secondary and Primary Sjögren's Syndrome in a Large Collection of Lupus Families (2015)
Systemic lupus erythematosus (SLE) and Sjögren's syndrome (SS) share clinical and immunogenetic features and may occur together. We undertook this study to determine the risk of primary SS among SLE-unaffected relatives of SLE patients and whether or not primary and secondary SS tended to occur in the same families. Methods. We collected clinical and serological data on 2694 SLE patients, 7390 SLE-unaffected relatives of the SLE patients, and 1470 matched controls. Results. Of the 2694 subjects with SLE, 548 had secondary SS, while 71 of their 7390 SLE-unaffected relatives had primary SS. None of the 1470 controls had SS as defined herein (p = 5 × 10-5 compared to SLE-unaffected relatives). Of the 71 SLE-unaffected relatives with primary SS, 18 (25.3%) had an SLE-affected family member with secondary SS, while only 530 of the 7319 (7.2%) SLE-unaffected relatives without SS did so (p = 1 × 10-8). Conclusion. Among families identified for the presence of SLE, primary and secondary SS tend to occur within the same families. These results highlight the commonalities between these two forms of SS, which in fact correspond to the same disease. © 2015 Rachna Aggarwal et al.